W/Cu thin film infrared reflector for TiNxOy based selective solar absorber with high thermal stability - Liu, Y. C. (2017)
The W/Cu thin film structure is deposited by magnetron sputtering to form the infrared reflector for the TiNxOy based selective solar absorber (SSA) that can be used in the low- and middle-temperature applications. The structural, chemical, and optical properties of the SSA layers that experienced thermal annealing at different temperatures for various durations have been investigated with the characterization techniques, including X-ray photoelectron spectroscopy, X-ray diffraction, atomic force microscopy, spectroscopic ellipsometry, and spectrophotometry. Without a W layer, the reflectance in both visible and infrared ranges of the SSA increases as a result of the crystallization of the Cu layer at elevated temperatures. With a W layer with appropriate film thickness, the increase of the reflectance in the visible range can be suppressed to maintain a high solar absorptance, whereas a high infrared reflectance can be maintained to achieve a low thermal emittance. It is shown that for the SiO2-TiNxOy-W-Cu-Glass SSA with a 15 nm W thin film, thermal annealing can significantly reduce the thermal emittance to a low value (e.g., 4.4% at the temperature of 400 °C for annealing at 400 °C for 6 h), whereas the solar absorptance can be maintained at a high value (e.g., 92.2% for the annealing at 400 °C for 6 h).